POTENSI TANAMAN TRANSGENIK UNTUK MENGATASI MASALAH KEKURANGAN GIZI GLOBAL - Nur Veryani, Andi; Hala, Yusminah (Jurnal Biogenerasi, 2024)
Malnutrition is a global problem that has serious impacts on public health, especially in developing countries, where access to nutritious food is often limited. One innovative solution to overcome this problem is through transgenic plant technology, which allows for increased nutritional content in food crops. This study aims to analyze the potential of transgenic plants as a solution to overcome the problem of global malnutrition. The method used in this study is a literature review, by reviewing scientific articles, research reports, and other relevant publications that discuss the development and application of transgenic plants. The results of the study indicate that several transgenic plants in the literature review, such as Golden Rice enriched with beta-carotene to increase vitamin A intake, corn with higher essential amino acids, omega-3 soybeans, and Orange-Fleshed Sweet Potato (OFSP) have great potential in overcoming specific nutritional deficiencies. This study concludes that transgenic plants can be part of a comprehensive solution to the problem of global malnutrition.